2003
DOI: 10.1177/0743558403254784
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Dating Violence Victimization and Psychological Well-Being

Abstract: This study assesses the relationship between adolescents' dating violence victimization and their psychological well-being. The participants were 190 high school students, ages 13 to 19 years, with just over half being boys (53%) and the remainder being girls (47%). Data were collected using self-administered questionnaires. For girls, increasing levels of dating violence (severity, frequency, injury) were related to higher levels of post-traumatic stress and dissociation, even after controlling for demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
148
5
12

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(174 citation statements)
references
References 41 publications
4
148
5
12
Order By: Relevance
“…In the present study, it was observed that the adolescents present high exposure to violence. In relation to the correlations found, the results are similar to previous findings which indicate an inverse association between violence and subjective well-being (Callahan et al, 2003;Park, 2004;Sarriera et al, 2012). At the same time, in considering that the greater perception of subjective well-being by the young people is associated with health and quality of life, it is emphasized that its promotion may serve as a resource for confronting and preventing violence among the young.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, it was observed that the adolescents present high exposure to violence. In relation to the correlations found, the results are similar to previous findings which indicate an inverse association between violence and subjective well-being (Callahan et al, 2003;Park, 2004;Sarriera et al, 2012). At the same time, in considering that the greater perception of subjective well-being by the young people is associated with health and quality of life, it is emphasized that its promotion may serve as a resource for confronting and preventing violence among the young.…”
Section: Discussionsupporting
confidence: 91%
“…It is important to be cautious in inferring causal relationships between violence and well-being, as the measurements of association used in this study are not appropriate for this type of conclusion. It may be thought that exposure to violence may both reduce the levels of well-being, due to the negative consequences that this can bring, and at the same time could raise the hypothesis that adolescents who already present lower levels of well-being may be more vulnerable to victimization, as in the discussion made by Callahan et al (2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical and Youth Life Satisfaction: A Review of the Literature 597 emotional abuse that occurs in an adolescent relationship can have a more harmful effect on psychological well-being than it does during adulthood, due to adolescents' lack of experience and resources in this area. For example, Callahan et al (2003) found a negative relationship between dating violence and LS for both boys and girls. Further, increases in dating violence were found to contribute to increased posttraumatic stress, anxiety, depression, and dissociation.…”
Section: Victimizationmentioning
confidence: 99%
“…Many young people report that they have been the victims of either physical or emotional violence during a dating relationship (Callahan et al 2003). Physical and Youth Life Satisfaction: A Review of the Literature 597 emotional abuse that occurs in an adolescent relationship can have a more harmful effect on psychological well-being than it does during adulthood, due to adolescents' lack of experience and resources in this area.…”
Section: Victimizationmentioning
confidence: 99%